GDM Alters Expression of Placental Estrogen Receptor α in a Cell Type and Gender-Specific Manner. (December 2015) - Knabl, Julia; Hiden, Ursula; Hüttenbrenner, Rebecca; Riedel, Christina; Hutter, Stefan; Kirn, Verena; Günthner-Biller, Margit; Desoye, Gernot; Kainer, Franz; Jeschke, Udo
Objective: The nuclear receptor estrogen receptor α (ERα) is one of the key players in energy balance, insulin resistance, and trophoblast differentiation. We tested the hypothesis that gestational diabetes mellitus (GDM) alters expression of placental ERα in a cell type-specific manner and that this regulation may involve epigenetic changes. Study Design: Expression of ERα was analyzed by immunohistochemistry using the semiquantitative immunoreactive score in 80 placentas (40 GDM/40 controls). Quantitative real-time polymerase chain reaction (PCR) measured ERα messenger RNA (mRNA) in decidual tissue. Methylation-specific PCR was performed to analyze cytosine-phosphatidyl-guanine-island methylation of the ERα promoter. Results: Expression of ERα protein is upregulated ( P = .011) in GDM in extravillous trophoblasts but not in syncytiotrophoblast. Gestational diabetes mellitus downregulated ERα in decidual vessels only in pregnancies with male but not female fetuses. Furthermore, mRNA of the ERα encoding gene estrogen receptor gene 1 ( ESR1 ) was increased (+1.77 fold) in GDM decidua when compared to controls ( P = .024). In parallel, the promoter of ESR1 was methylated only in decidua of healthy control individuals but not in GDM. Conclusion: Gestational diabetes mellitus affects expression of placental ERα in a cell type-dependent way, on epigenetic level. These data link GDM with epigenetic deregulations of ERα expression and open new insights into the intrauterine programming hypothesis of GDM.